2018
DOI: 10.1371/journal.pone.0200889
|View full text |Cite
|
Sign up to set email alerts
|

Medical waste management in three areas of rural China

Abstract: ObjectiveThe purpose of this paper is to describe current practices of medical waste management, including its generation, investments, collection, storage, segregation, and disposal, and to explore the level of support from upper tiers of the government and health care system for medical waste management in rural China.MethodsThe authors draw on a dataset comprised of 209 randomly selected rural township health centers (THCs) in 21 counties in three provinces of China: Anhui, Shaanxi and Sichuan. Surveys were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…The present and the previously conducted studies suggested that HCW segregation practice requires special attention, and if the segregation process is poor or even a very small amount of hazardous waste is added to the general waste category, then the entire mass of the general waste can be unnecessarily polluted by the hazardous waste [16]. In line with this, several studies conducted in Uganda [32], Sudan [37], Iran [38], Jordan [39], Nigeria [40], and China [41] reported poor HCW segregation practice among healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
“…The present and the previously conducted studies suggested that HCW segregation practice requires special attention, and if the segregation process is poor or even a very small amount of hazardous waste is added to the general waste category, then the entire mass of the general waste can be unnecessarily polluted by the hazardous waste [16]. In line with this, several studies conducted in Uganda [32], Sudan [37], Iran [38], Jordan [39], Nigeria [40], and China [41] reported poor HCW segregation practice among healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
“…GARCÍA-UBAQUE; ZAFRA-MEJÍA, TRAN et al, 2019;FARROKHI et al, 2016;ANOZIE, 2017;AHMAD et al, 2019;URIOSTE et al, 2018;MARCZAK, 2016;AUGUSTIN et al, 2016;FARZADKIA et al, 2018;JOVANOVIĆ et al, 2016;GAO et al, 2018;KRISHNAN;DEVAMANI;JAYALAKSHMI, 2015;OLIVEIRA;VIANA;CASTAÑON, 2018;PRAYITNO et al, 2018;THANH et al, 2016;SREEREMYA;RAJIV, 2017;NOGUEIRA et al, 2018;KUCHIBANDA;MAYO, 2015;YOUSEFI;AVAK ROSTAMI, 2017;NEVEU C;MATUS C, 2007;AL-MOMANI et al, 2019;PACHAURI et al, 2019;AFOLABI et al, 2018;DEWI et al, 2019;NJUANGANG;LIYANAGE;AKINTOYE, 2018;KIM et al, 2018;MUKHAIBER, 2017;JASEM;JUMAHA;GHAWI, 2018;GARIBALDI et al, 2017;NAMBURAR et al, 2018).…”
Section: Resultados E Discussõesmentioning
confidence: 99%
“…Biomedical waste handling is a sensitive process, which requires a high standard of preparation [2]. It requires a specific training that depends on the nature of the work in the hospital, the hazard and worker experience, and also the responsibilities of individual workers [3].…”
Section: Level Of Awarenessmentioning
confidence: 99%
“…In recent years, amount of waste generated by society has increased drastically following the trends of population raise [1,2]. The production of waste materials is referred as the waste stream and includes the entire variety of refused waste from domestic, industrial, construction and commercial processes [3,4].…”
Section: Introductionmentioning
confidence: 99%